Benzo[b]fluoranthene Impairs Mouse Oocyte Maturation via Inducing the Apoptosis - Guo, Jin; Zhang, Liqun; Li, Chong; Qin, Yinhua; Liu, Weiwei; Li, Jingyu; Huang, Guoning (Frontiers in Pharmacology, 2020)
Benzo[b]fluoranthene (BbF) is one of the main pollutants of polycyclic aromatic hydrocarbons (PAHs), which are generated from organic materials combustion and diesel exhaust. It has been reported that after maternal exposure, BbF crosses the placental barrier, leading to offspring defects. However, the effect of BbF on the female reproductive system, especially on oocyte maturation has not been studied. To elucidate the effect and precise mechanism of BbF on oocyte maturation, nuclear and cytoplasm maturation were evaluated after exposing mouse oocytes to different concentrations of BbF. Results showed that BbF exposure shows no effect on the meiotic progression, but it caused defects on nuclear maturation via impairment on chromosome alignment. In addition, the treatment of BbF displayed the defects on the cytoplasmic maturation by leading to the mitochondrial dysfunction, DNA damage accumulation, early apoptosis and the loss of H3K4me3. To investigate the mechanism, we found that BbF impaired the oocyte maturation via the AMPK pathway. BbF exposure caused the phosphorylation of AMPK, which cause the DNA damage accumulation and apoptotic incidence. Taken together, our results demonstrated that BbF exposure impaired the mouse oocyte maturation due to mitochondrial dysfunction and early apoptosis.